A new research strategy for integrating studies of paleoclimate, paleoenvironment, and paleoanthropology. Issue 2 (4th March 2015) - Marean, Curtis W.; Anderson, Robert J.; Bar‐Matthews, Miryam; Braun, Kerstin; Cawthra, Hayley C.; Cowling, Richard M.; Engelbrecht, Francois; Esler, Karen J.; Fisher, Erich; Franklin, Janet; Hill, Kim; Janssen, Marco; et al.
Abstract : Paleoanthropologists (scientists studying human origins) universally recognize the evolutionary significance of ancient climates and environments for understanding human origins.1 2 3 4 5 6 Even those scientists working in recent phases of human evolution, when modern humans evolved, agree that hunter‐gatherer adaptations are tied to the way that climate and environment shape the food and technological resource base.7 8 9 10 The result is a long tradition of paleoanthropologists engaging with climate and environmental scientists in an effort to understand if and how hominin bio‐behavioral evolution responded to climate and environmental change. Despite this unusual consonance, the anticipated rewards of this synergy are unrealized and, in our opinion, will not reach potential until there are some fundamental changes in the way the research model is constructed. Discovering the relation between climate and environmental change to human origins must be grounded in a theoretical framework and a causal understanding of the connection between climate, environment, resource patterning, behavior, and morphology, then move beyond the strict correlative research that continues to dominate the field.